Enhancing Core Industry Placements Through Internships: A Strategic Ecosystem Model for Engineering Education in India - Dapkekar, Amol; Aalam, Zahir; Mane, Rupali (Journal of Neonatal Surgery, 2025)
One of the largest and most skilled young labour pools in the world is found in India, where a sizable percentage of students hope to work in core engineering sectors. By providing students with practical experience, technical expertise, and professional acumen, internships are an essential tool for bridging the gap between academic learning and industry demands. Numerous private institutions under-promote or under-support internships, which has a negative impact on placement results despite AICTE's mandate. Additionally, companies are still hesitant to make offers to tier-2 and tier-3 colleges, and students frequently miss out on internship opportunities. The multifaceted role of internships in improving core industry placements is examined in this study, which also suggests a comprehensive model for internship enhancement based on industry, government, institutional, and student interventions. With its strategic frameworks and ecosystem visuals, the paper provides stakeholders with an actionable road map.